Technical training in the taekwondo. His fundamental characteristics (Review) (Revista científica Olimpia, 2021)
The epistemic breaches detected in the taekwondo's process of technical training and his incidence in the basic elements, music motives that they enabled directing the sketch of the criteria manifested in teaching – learning of this sports discipline, therefore, his importance was once the contribution was hit on to the especial didactics, when printing one of his formative characters, contextualized and sequential logician on an integral focus's base. Besides, from the theoretic renewal, a process of dialectic and global way that it enables could conceive acquiring resources like knowledge, abilities and attitudes itself. You attempted like objective: Penetrating into the epistemic inwardnesses of the process of technical training of the taekwondo as from the criteria, or fundamental characteristics during teaching learning of the basic elements whose reach, refer the systematization of the theoretic assumed sources and examined for the pedagogic organization to develop in an immediate future.
Keywords: taekwondo, technical training, characteristics, teaching learning